Influence of the Molar Mass and Concentration of the Polyvinylpyrrolidone on the Physical–Mechanical Properties of Polylactic Acid for Food Packaging - Guarda-Moraga, A; Velasquez, E (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
Improving the end-of-life performance of polylactic acid (PLA) for food packaging requires strategies that enhance biodegradability, solubility, and dispersibility without compromising essential material properties. PLA-based films were produced by melt extrusion using polyvinylpyrrolidone (PVP) as a hydrophilic modifier, aiming to enhance the water uptake and affinity of PLA, which may potentially lead to faster environmental degradation. Two PVPs with distinct molar masses at varying concentrations were used to investigate their effects on the structural, thermal, mechanical, optical, and barrier behavior of the films. Thermal analysis revealed a slight depression in glass transition temperature, more evident in blends with low-molecular-weight PVP10, indicating increased chain mobility and partial miscibility. A two-step degradation process with extended thermal decomposition profiles was observed upon the inclusion of PVP. SEM and ATR-FTIR analyses confirmed enhanced dispersion and non-covalent interactions in PVP10-based blends, in contrast to the pronounced phase separation and micro-voids observed in PVP40-based systems. Mechanically, films containing 5 and 10 wt.% of PVP10 retained tensile strength and stiffness, whereas PVP40 led to embrittlement. Optical properties were modified by increasing the PVP content, resulting in greater opacity and color differences, which potentially offer benefits for light-sensitive packaging. Altogether, PLA films containing 5 and 10 wt.% of PVP10 demonstrated the most favorable balance between water affinity-oriented design and packaging-relevant performance. © 2025 by the authors.